Novel low-εr and lightweight LiBO2 microwave dielectric ceramics with good chemical compatibility with silver. Issue 11 (September 2022) - Yin, Changzhi; Du, Kang; Zhang, Meng; Yang, Jiaqing; Wang, Fei; Guo, Yanbo; Cheng, Mingfei; Cai, Yiyang; Song, Xiaoqiang; Khaliq, Jibran; Li, Chunchun; Lei, Wen; et al.
Abstract: High-speed signal propagation systems require dielectric ceramics with low relative permittivity (εr ) and a high-quality factor ( Qxf ). In this paper, a novel low-permittivity borate ceramic (LiBO2 ) was synthesized using a conventional solid-state reaction method. Based on the X-ray diffraction and Rietveld refinement, the LiBO2 crystallized into a monoclinic structure with a space group of P21/c. Dense and single-phase ceramic was obtained at 640 °C with comprehensive microwave dielectric properties: a low relative permittivity ( ε r ) of 5.3, a moderate quality factor ( Q × f ) of 18, 200 GHz at 16.3 GHz, and a temperature coefficient of resonant frequency (τ f ) of − 66.2 ppm/°C. Good chemical compatibility with Ag electrode and thermal expansion coefficient of 25.4 ppm/°C was achieved demonstrating the potential applications as dielectric resonances in wireless communications and substrates in low-temperature cofired ceramics.